Differentiation and validation of mild and severe strains of citrus tristeza virus through codon usage bias, host adaptation, and biochemical profiling - Khatoon, Halima; Chavan, Dharmappa D.; Meena, Vijay Kamal; Kashyap, Abhijeet Shankar; Sathiyaseelan, Kumar; Elangovan, Marimuthu; Patil, Lalit; Meena, Bharat Raj; Gauns, Aarti; Bhattacharyya, Utpal Kumar; Biswas, Kajal Kumar (Frontiers in Microbiology, 2025)
Citrus tristeza virus (CTV) is one of the most economically significant citrus pathogens, causing epidemics worldwide. It comprises strains ranging from asymptomatic mild variants to highly virulent severe forms. However, the molecular basis distinguishing mild from severe strains remains poorly characterized. To understand these mechanisms, a total of fifty eight citrus samples were screened using RT-PCR targeting the coat protein gene, with forty seven testing positive for CTV. Analysis of Codon Usage Bias (CUB) revealed that both mutation pressure and natural selection influence codon preferences, with natural selection playing the dominant role. Hierarchical clustering dendrogram based on Effective Number of Codons (ENc) values reveals twenty mild-like isolates and twenty seven severe strains. Among the mild-like group, nine mild strains exhibited higher Codon Adaptation Index with uracil at the third codon position and Relative codon usage patterns closely aligned with the Host, suggesting greater translational efficiency and reduced virulence. Quantitative RT-PCR confirmed lower viral accumulation in plants infected with mild strains, with a ninefold increase observed in those infected by severe strains. Validation through biological indexing confirmed the mild nature of these isolates and their ability to confer cross-protection upon challenge with severe strains. Phylogenetic relationships and sequence identity metrics indicated a close genetic association of mild strains with the VT strain, highlighting their genetic relatedness. Additionally, biochemical profiling revealed distinct patterns in sugar, phenol, antioxidant, and chlorophyll levels across mild, severe, and healthy plants. These findings highlight the promise of mild, well-adapted CTV strains as effective agents for cross-protection in citrus orchards.